DISEASES OF NATURAL RUBBER (HEAVEA BRASILENSIS) INDUCED BY THE CLIMATIC ELEMENTS OF RAINFALL AND TEMPERATURE IN IKPOBA-OKHA LOCAL GOVERNMENT AREA OF EDO STATE, NIGERIA - ABRAHAM EHIZOJIE ILENRE (International Studies Journal)
This paper examined the diseases of natural rubber (Heaveabrasilensis) induced by the climatic elements of rainfall and temperature in Ikpoba-Okha Local Government Area of Edo State, Nigeria. The paper identified the varieties of natural rubber cultivated in the study area, the diseases of natural rubber induced by the climatic elements of rainfall and temperature in the study area, the level of awareness of natural rubber farmers on the impact of the climatic elements on natural rubber production in the study area and the problems induced by the climatic elements of rainfall and temperature on natural rubber production in the study area. To achieve these objectives, the researcher used both primary and secondary research methods to collect the data used for the study. In the study area, a total of five hundred and fifteen (515) structured questionnaires representing 0.1% of the projected population for 2023, which is, 515,042 were administered directly by the researcher to the respondents in the study area.  The secondary data used were obtained from National Population Commission (NPC), Agricultural Development Programme (ADP) and the Ministry of Agriculture and Natural Resources (MANR).The data obtained were analysed using tables, percentages and degrees. The results showed the varieties of natural rubber cultivated in the study area. The study also reveals the diseases of natural rubber induced by the climatic elements of rainfall and temperature in the study area. The problems associated with the diseases were also revealed. The following recommendations are made: effective disease management strategies, monitoring of climatic conditions, incorporating resistant natural rubber clones and improving cultural practices, sustainable practices to manage diseases, governments’ intervention to encouragenatural rubber farmers annually. This paper is therefore concluded by advising the governments at all levels to implement the recommendations made by the researcher.